Determinant Factors of Immunization Coverage in Toddlers Under 5 Years Old in Banda Aceh, Indonesia: Cross Sectional Study - Masyudi Masyudi; Said Usman; Salfauqi Nurman; Ismail Ismail; Abubakar Abubakar (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of this research is to determine the factors related to providing complete basic immunization to toddlers in the working area of ​​the Meuraxa Health Center, Banda Aceh. This research is analytical by design cross sectional. The population in this study were all mothers who had toddlers in the working area of ​​the Meuraxa Health Center in 2023, totaling 1860 people and a sample of 95 people. The research was conducted from 7 to 15 June 2023. Data was processed univariate and bivariate. The research results showed that there was a relationship between knowledge (P value = 0.006), there was a relationship between attitudes (P value = 0.000), there was a relationship between health education (P value = 0.003) and there was a relationship between the role of religious leaders (P value = 0.003) with the provision of complete basic immunization in toddlers at Meuraxa Community Health Center, Banda Aceh City in 2023. The Community Health Center can provide routine outreach to the community, especially mothers who have babies, either individually or in groups. Increase the support of religious figures for immunization by involving them in every immunization activity and making religious figures partners in disseminating immunization information